Neutralization Of The National Police In The General Election In Maintaining The Collapse Of The Unitary State Of The Republic Of Indonesia - Hasibuan, Edi Sahputra (Faculty of Law, Universitas Pekalongan, 2024)
The glue in democracy, especially in the run-up to the 2024 elections, is a stronger civilian authority accompanied by optimal parliamentary oversight, and the creation of professional security actors (military and police).